The public charge rule and program participation among U.S. citizens - Kristin F. Butcher; Luojia Hu; Ryan Perry (Federal Reserve Bank of Chicago, 2024)
Use of public assistance by noncitizens is controversial. Before 2018, institutionalization and receipt of cash benefits were considered as evidence of whether immigrants were likely to become a "public charge" and, therefore, ineligible for citizenship. But a new rule-proposed in 2018 and finalized in 2020-also made participation in SNAP/food stamps and Medicaid relevant as evidence. We examine whether participation in SNAP/food stamps and Medicaid among U.S.-born children-whose own eligibility for program participation should be unaffected by the new rule-has changed, based on the citizenship status of their parents. We find evidence that, after the 2018 proposal, U.S.-born children with noncitizen parents are less likely than the children of U.S.-born parents to participate in these programs. We discuss the literature on "chilling effects" and on the impact of safety net programs on children's long-term outcomes.
Keywords: I13; I3; I38; J15; 330; immigration; safety net; public charge rule; SNAP/Food Stamps; Medicaid; Medicare